Uptake of Pu(IV) by hardened cement paste in the presence of gluconate at high and low ionic strengths - Stietz, J.; Amayri, S.; Häußler, V.; Prieur, D.; Reich, T. (Frontiers in Nuclear Engineering, 2023)
The uptake of Pu(IV) by hardened cement paste (HCP) at degradation state I was investigated in the absence and presence of gluconate (GLU). Furthermore, the influence of the ionic strength was examined in different background electrolytes. Artificial cement pore water (ACW, pH = 13) was used for low ionic strength (I = 0.3 M), and cement pore water based on the diluted caprock solution (ACW-VGL, pH = 12.5) was used for high ionic strength (I = 2.5 M). Sorption experiments were performed under an Ar atmosphere using HCP in the HCP/GLU binary system ([GLU]0 = 1 × 10−1–1 × 10−8 M) and the HCP/Pu(IV)/GLU ternary system ([239Pu(IV)]0 = 1 × 10−8 M, [GLU]0 = 1 × 10−2 M) with solid-to-liquid (S/L) ratios of 0.5–50 g L–1 within a contact time of 72 h. GLU sorbs strongly on HCP; a saturation of the sorption sites of HCP with GLU was observed at [GLU] ≥ 1 × 10−4 M at S/L = 5 g L–1. The effects of the order of addition of the components Pu(IV) and GLU on the sorption of Pu(IV) on HCP were investigated. In the absence of GLU, a quantitative uptake (S% ≥ 99%) of Pu(IV) by HCP was observed, independent of the ionic strength of the background electrolytes. In the presence of 1 × 10−2 M GLU, the sorption of Pu(IV) on HCP was significantly lower. For X-ray absorption fine structure (XAFS) measurements, powder samples with Pu ([239Pu(III)]0 = 5 × 10−6 M) sorbed on HCP (S/L = 2.5 g L–1) were prepared at pH ≈ 13 in ACW and ACW-VGL, respectively. One additional sample was prepared in the presence of GLU ([GLU]0 = 1 × 10−2 M) with ACW-VGL as the electrolyte for comparison. Pu LIII-edge X-ray absorption near-edge structure (XANES) spectra show that Pu is in the tetravalent oxidation state after being taken up by the HCP. The structural parameters obtained from extended X-ray absorption fine structure (EXAFS) analysis and comparison with literature indicate incorporation of Pu(IV) into the calcium-silicate-hydrate (C-S-H) phases of HCP. The different ionic strengths and the presence of GLU had no influence on the near-neighbor environment of Pu in HCP.